ANALISIS MIGRASI KADAR BISFENOL-A (BPA) PADA GALON POLIKARBONAT (PC) KE LARUTAN SIMULAN ETANOL MENGGUNAKAN HPLC DI KABUPATEN MANOKWARI - Faizaan Ahmad; Markus Heryanto Langsa; Bertha Mangallo; Aan Sulistiawan Aan Sulistiawan (FMIPA Universitas Papua, 2025)
Polycarbonate (PC) gallon containers are known to contain Bisphenol-A (BPA), a compound that may migrate into the water and pose health risks, particularly when exposed to high temperatures. This study aims to analyze the migration levels of BPA from No. 7 PC gallon containers into a 20% ethanol simulant solution, reflecting the conditions of products circulated in Manokwari Regency. Samples were incubated at 60°C for two different durations: 2 hours and 10 days. The analysis was performed using High-Performance Liquid Chromatography (HPLC) with a fluorescence detector. The results indicated that incubation time affected BPA migration levels. No BPA migration was detected after 2 hours of incubation; however, after 10 days, BPA was detected at concentrations ranging from 0.007 to 0.017 ppm. Furthermore, an analysis of 18 No. 7 PC gallon samples available in the Manokwari market showed that all samples contained BPA, with concentrations ranging from 0.005 to 0.185 ppm. All detected BPA levels remained below the maximum limit set by the Indonesian National Agency of Drug and Food Control (BPOM Regulation No. 20 of 2019), which is 0.6 ppm.